3a-5+a=6a+5-2a

Simple and best practice solution for 3a-5+a=6a+5-2a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-5+a=6a+5-2a equation:



3a-5+a=6a+5-2a
We move all terms to the left:
3a-5+a-(6a+5-2a)=0
We add all the numbers together, and all the variables
3a+a-(4a+5)-5=0
We add all the numbers together, and all the variables
4a-(4a+5)-5=0
We get rid of parentheses
4a-4a-5-5=0
We add all the numbers together, and all the variables
-10!=0
There is no solution for this equation

See similar equations:

| 3a-5+a=6@+5-2a | | 7(2-3d)=56 | | -60-9n=5+3n | | P(x)=75x-500 | | -7-4v=8v+60 | | 3x2=3 | | 23x^2=19 | | 2y^2=-162 | | 7z+8=2z-26 | | 5(r-3)=2(r+6) | | √x-4=1 | | 2(x+3)-(x-2)=5 | | 8w+12=3w+46 | | 6-3x=5-7x | | 6y+12=2y-34 | | 50-3v=2v+5 | | 3y-5y+11=17 | | 2z+5=4z-15 | | 4y+5=5y-12 | | 7x-1=x-1 | | 3+7v+8=-17 | | 3x8=-4 | | 12+5•(4-5x)=32 | | 2(2x+5)/7=3x-4/6+5/3 | | -3(4-2c)=18 | | 3x-3=11x-66 | | (z+25)^2=5 | | 6=(-2g-1)=-(13g+2) | | x^2=9600 | | x^=9600 | | -3(y/3+1)-2=4*(1-y) | | 9b2-54b-54=-135 |

Equations solver categories